Faktor-Faktor Yang Mempengaruhi Kejadian Stunting Di Upt Puskesmas Lumban Sinaga Kecamatan Pangaribuan Kabupaten Tapanuli Utara Tahun 2023 - Pakpahan, Leonardo; Manurung, Kesaktian; E Sitorus, Mido; Ketaren, Otniel; Lina Tarigan, Frida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Stunting is one of the chronic nutritional problems that remains a global concern, especially in developing countries such as Indonesia. This study aims to identify factors associated with the incidence of stunting in the Puskesmas Lumban Sinaga Pangaribuan District, North Tapanuli Regency. This study is an onservational analytic study with a Case Control approach. This research was conducted from October 2023 to February 2024. The sample in this study were all mothers who had stunting toddlers as many as 75 cases(total population) control samples as many as 75 toddlers who did not suffer from stunting. Data collection using questionnaires and analyzed using logistic regression tests. The results showed that exclusive breastfeeding history (p 0.000), family income (p 0.013), maternal education (p 0.007), parity (0.000) and maternal height (p 0.000) had a significant relationship with the incidence of stunting. It is concluded that the factors associated with the incidence of stunting at the Lumban Sinaga Health Center are exclusive breastfeeding history, family income, maternal education, parity and maternal height with the dominant factor being maternal height. It is recommended for mothers to provide exclusive breastfeeding to babies for the first 6 months of life and continue breastfeeding with complementary foods until the age of 2 years to meet nutritional and immunity needs that are important for optimal growth.